Avaliação da qualidade proteica, peso de órgãos e comprimento da tíbia e animais experimentais alimentados com quinoa (Chenopodium, quinoa) - Eliane Maria Ribeiro; Juliana Márcia Macedo Lopes; Ivy Scorzi Cazelli Pires; Lucilene Soares Miranda; Vanessa Alves Ferreira; Iara Ribeiro; Letícia Aparecida Gonçalves (Universidade do Estado do Rio de Janeiro, 2022)
Objective: The aim of this work was to evaluate the protein quality and the effects of quinoa (Chenopodium quinoa) ingestion on liver, spleen and tibial length in experimental animals. Method: For analysis of protein quality and feed efficacy, a 28-day biological assay and 18 Wistar rats were used, calculating the protein efficiency coefficient (PER), net protein ratio (NPR), chemical score corrected for protein digestibility (PDCAAS), utilization of liquid protein (NPU), in vivo digestibility and food efficiency coefficient (CEA) (AOAC). Results: Significant differences were found between PER, NPR, NPU and CEA values for quinoa (0.54; 2.58; 26.22 and 0.05, respectively) and casein (2.04; 3.84; 59 .9; 0.2, respectively). As for the proximate composition, values of 11.31% of protein, 11.28% of moisture, 2.04% of ash, 7.9% of lipids and 67.47% of carbohydrates were found. No significant differences were found between digestibility values of casein (96.93%) and quinoa (92.2%). The PDCAAS value found for quinoa was 0.97. There were significant differences in relation to organ weights, except for the weight of the tibia, with casein having greater weight. Conclusion: The lowest PER, NPR, NPU and CEA values demonstrated that quinoa protein had a lower quality than milk, but that the digestibility and PDCAAS values prove that it has good protein quality and an interesting amino acid profile, requiring further studies to assess its nutritional value.